FRI0645-HPR Frequently Asked Questions of Patients with Osteoarthritis: A Consensus Exercise. (15th July 2016) - Claassen, A.; Koëter, S.; Botman, J.; Schers, H.; van den Ende, C.; ,
Abstract : Background: Providing unambiguous information about osteoarthritis (OA) and describing options for self-management help patients to become actively involved in their own care. The lack of consensus among clinicians and the heterogeneous terminology between involved disciplines may complicate effective communication. Therefore, we decided to develop an educational course based on a structured inventory of informational needs and on consensus-based information addressing those needs. Objectives: 1) to make an inventory of the most frequently asked questions (FAQs) on OA, expressed by patients to their different health care providers, 2) to formulate answers based on consensus among health care providers in the area of Nijmegen. Methods: To identify and formulate answers to FAQS the following steps were taken: 1) Orthopaedic surgeons, rheumatologists, nurse practitioners from 3 different hospitals, and general practitioners and physiotherapists participating in a local network, were invited to provide 5–10 FAQs, not covered by a website providing information on OA (ran by The Dutch College of General Practitioners). Additionally the Dutch Arthritis Foundation was asked to provide FAQs from their arthritis helpline. 2) After deleting overlapping FAQs, the remaining FAQs were categorized by two researchers. 3) Care providers who provided FAQs and patients (responding to a call on various websites of local patient organisations) were asked to indicate a top 5 of most important FAQs per category and divide 100 points among their top 5 per category. 4) Twenty most important FAQs were selected for answer formulation. Then, for each FAQ 3 care providers from 3 different disciplines were asked to formulate an answer. 5) Finally, in consensus meetings draft answers were combined into one final answer per FAQ. Results: A total of 28 responders provided 192 FAQs. From these FAQs, 93 overlapping FAQs were deleted and remaining 99 FAQs were categorized into 9 categories of 7–14 FAQs each, namely: "OA; cause, symptoms and disease course", "diagnostics", "medication", "care providers", "lifestyle", "surgery", "work", "self-management", "other". Seventeen professionals and 29 patients responded to the subsequent round of prioritising. The overall top 5 FAQs were: 1."What are the newest treatment options?" 2. "What is the natural course of OA?" 3. "If medication does not work, what other treatment options do I have?" 4. "'What sports are suitable? At what frequency and intensity?" 5. "When am I eligible for a joint replacement?". In 3 meetings the project group reached consensus on answers of the Top-20 FAQs. Conclusions: Our study shows that it is feasible to achieve consensus among disciplines on information on topics not covered by guidelines, which can help to overcome communication hazards between patient and professionals from different disciplines. Formulated answers have been used in the development of an OA educational self-management course for OA-patients. Future research is necessary to examine to what extent consistency of information can contribute to self-management. Disclosure of Interest: None declared